Fabrication and investigation of P3HT:PCBM bulk heterojunction based organic field effect transistors using dielectric layers of PMMA:Ta2O5 nanocomposites - Canımkurbey, B.; Kösemen, Z. A.; Çakırlar Ç.; San S.E.; Yasin M.; Berber S.; Kösemen A. (Elsevier B.V., 2017)
In this work, we have fabricated top-gate/bottom-contact type Organic Field Effect Transistors (OFETs). A poly(3-hexylthiophene) (P3HT): [6,6]-phenyl C61-butyric acid methyl ester (PCBM) blend with 1:1 wt/wt ratio was used as the semiconducting layer, and poly(methyl methacrylate)(PMMA):Ta2O5 blends with varying concentration of Ta2O5 were used as dielectric layers of the devices. Interdigitated type source-drain electrodes on a glass substrate were coated with a semiconducting layer, which was followed by the deposition of dielectric layer and a top aluminum gate contact in sequence. Dielectric layers were prepared as the blends of PMMA:Ta2O5 with Ta2O5 wt/wt concentrations of 0%, 3%, 7%, 10%, 20% and 50%. Structural and electrical characterization of PMMA:Ta2O5 nanocomposite films were carried out using scanning electron microscope (SEM) and dielectric analyzer respectively. Dielectric constant of PMMA:Ta2O5 nanocomposites was found to increase with the increasing concentration of Ta2O5. Devices that were processed using 0 wt% and 3 wt% concentration of Ta2O5 exhibited a typical p-type OFET behavior with hole mobility of 2.68 × 10? 3 and 3.42 × 10? 3 cm2/Vs respectively. Whereas, the devices with 7 wt% and higher concentration of Ta2O5 showed electron mobility in addition to hole mobility, indicating ambipolar behavior of the devices. Furthermore, electron mobility was found to increase with increasing concentration of Ta2O5. The hole and electron mobility values were found to be 1.08 × 10? 3 and 4.42 × 10? 3 cm2/Vs at 50% wt concentration of Ta2O5 respectively. Based on excellent saturation behavior and promising mobility values of the investigated solution processed devices, it is expected that the investigated devices can possibly be utilized in some practical applications, such as low-cost large area sensing arrays in future. © 2017 Elsevier B.V.
Keywords: Ambipolar; Mobility; OFETs; P3HT; PCBM; PMMA; Saturation; Ta2O5